The Validity of the Condition of Payment of Certain Property in the Liability Contract - Gholamreza Yazdani (آموزه‌‌های فقه مدني, 2020)
Under the guarantee contract, the guarantor’s obligation is indebted to the person whom a guarantee is given (creditor), and the right of the creditor is granted to the guarantor’s obligation, the creditor does not have any objective (tangible) right to the guarantor’s property. The guarantor, in the releasement of the obligation of his or her own, determines the property of his/her property and pays it to the to the person whom a guarantee is given (creditor). The creditor is free to choose (disjunctive) any example of his/her property. Now, if during the guarantee contract, it is provisioned that the guarantor pays a certain amount of money to the creditor, what is the condition of such a provision in terms of validity and nullity? In this matter, there is a difference of opinion among the jurists. One group absolutely considers the condition to be valid, and another group has ruled that it is invalid, and another group considers the issue to be detailed way (including all particulars). In the present article, the author, using the library method and based on the analytical-descriptive method, has come to the conclusion that the condition of payment from a certain property, whenever it is foreseen as a condition in the proviso of guarantee contract (condition as an integral part of contract); the condition and contract are correct, but if they are as a qualification (provision) of contract, both the contract and the condition are null (void). Furthermore, if the condition of payment from a certain property is given to the same object from the very beginning so that the guarantor is not engaged as a result of the guarantee contract, then both the contract and the condition will be void.